KARAKTERISKTIK EKSEKUTIF, KOMPENSASI EKSEKUTIF, DAN SISTEM PERPAJAKAN SERTA PENGARUHNYA TERHADAP PENGHINDARAN PAJAK (Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia 2012-2014 - Hanan Asrawi (AKT 16 UMY 029, 2016)
haracteristics of executives, executive compensation, and the tax system against tax avoidance. This analysis uses the independent variable wich is characteristic of executives, executive compensation and the taxation system. The dependent variable is tax avoidance. The sample used in this research was annual reports of all company listed on Indonesia Stock Exchange. The sample was taken using the method of purposive sampling, and those met the selection criteria were taken. The sample used was of 21 firms. The statistics method used was multiplied analysis linear regression, with hypotheses testing of statistic t and F tests. The results of the analysis based on the use of all the independent variables indicated that the characteristics of the executive and executive compensation has significant effect on tax avoidance, while the taxation system showed negative and insignificant impact on tax avoidance. Keywords: tax avoidance; characteristics of the executive; executive compensation; taxation system.